If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 8 + -6x = -6 Reorder the terms: 8 + 8x + -6x = -6 Combine like terms: 8x + -6x = 2x 8 + 2x = -6 Solving 8 + 2x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 2x = -6 + -8 Combine like terms: 8 + -8 = 0 0 + 2x = -6 + -8 2x = -6 + -8 Combine like terms: -6 + -8 = -14 2x = -14 Divide each side by '2'. x = -7 Simplifying x = -7
| 25z-15=6z-24 | | 4=2(g-11)-2 | | (-7p)3= | | 2=7x-26 | | 15-g=6 | | -6+3(-8x+1)=15 | | 3(f-8)=-24 | | .04m=.08 | | 5t(10-3t)= | | 7/x-4=14/6 | | -5(4x-1)=-3x-6 | | 7-k=5 | | -7x-13+9x-19=-4 | | -1=2(j-8)+1 | | 10(s-6)=-146 | | 32-4x=18-6x | | 10y^2+90y=0 | | H=15t-4.9t^2+3 | | -2(8x+3)=3x | | 4x-x=7squared | | 2n-8+6n=-14+8n | | 2z-15+3z=5-5z+10 | | 4(b-12)+1=17 | | 2x+32=60 | | 11+3x=15+9x-3x | | 2(m+1)+2=10 | | X-5x=6-2x+5 | | -24x+18=4 | | 3v+6=0 | | -7+x=7+9-5 | | -16=5v+11 | | 9x+6=3(x-4) |